The Epidemiology and Economic Burden of Obesity and Related Cardiometabolic Disorders in the United Arab Emirates: A Systematic Review and Qualitative Synthesis. (3rd December 2018) - Radwan, Hadia; Ballout, Rami A.; Hasan, Hayder; Lessan, Nader; Karavetian, Mirey; Rizk, Rana
Abstract : Background . Noncommunicable diseases (NCDs) are considered as a global health problem and considered as a public health priority with the more considerable increasing trend of obesity and cardiometabolic disorders rates in the Middle Eastern countries. This systematic review aims at assessing the prevalence, incidence rates, and trends, as well as the cost of obesity and related cardiometabolic disorders in the United Arab Emirates (UAE). Methods . A highly sensitive strategy was used to retrieve original observational studies, addressing the epidemiology and cost of obesity and related cardiometabolic disorders in the UAE, irrespective of nationality (nationals and expatriates). The search was conducted on April 4, 2017, within numerous electronic databases and the grey literature. Standardized and validated methods were used for data extraction and analysis as well as quality assessment. Results . 6789 records were retrieved, of which 36 were deemed eligible. High prevalence rates were reported for obesity, diabetes, hypertension, and metabolic syndrome in all studies. However, the definitions and methods employed by the studies were highly variable. The risk of bias in the epidemiological studies ranged between low and medium. Only one study reported the cost of illness for diabetes. In this study, the estimated cost per patient was 2, 015 (adjusted to the year 2015), and it became twofold and sixfold higher in patients with microvascular and macrovascular complications, respectively. Conclusions . Obesity and related cardiometabolic disorders are highly prevalent in the UAE, but quoting a precise prevalence for them is difficult given the methodological heterogeneity of the epidemiological studies addressing them. Nonetheless, we detected a 2-3-fold increase in the prevalence of overweight and obesity in the UAE between 1989 and 2017. It is hopeful that this systematic review will provide an insight into direct future studies, especially longitudinal studies exploring obesity and cardiometabolic risks and their costs.